The Administration of Cortisol Induces Female-to-Male Sex Change in the Protogynous Orange-Spotted Grouper, Epinephelus coioides - Chen, Jiaxing; Peng, Cheng; Yu, Zeshu; Xiao, Ling; Yu, Qi; Li, Shuisheng; Zhang, Haifa; Lin, Haoran; Zhang, Yong (Frontiers in Endocrinology, 2020)
In this study, we injected cortisol into the protogynous orange-spotted grouper (Epinephelus coioides) to investigate the role of this hormone in sex change. Following injection, we evaluated gonadal changes, serum levels of steroid hormones, and sex-related gene expression during the processes of cortisol-induced sex change and cortisol withdrawal in the orange-spotted grouper. Cortisol treatment caused the degeneration of oocytes and induced sex change in a dose-dependent manner. Over the long-term, we observed a significant increase in serum 11-ketotestosterone (11-KT) levels in all cortisol-treated groups, although levels of 17β-estradiol did not change significantly. Consistent with the elevation of serum 11-KT levels, the expression of genes related to testicular development was also significantly up-regulated in the cortisol-treated groups. Based on our results, we propose that cortisol may trigger masculinization by inducing the synthesis of 11-KT and by directly activating the expression of sex-related genes. Furthermore, we found that cortisol-induced sex change was not permanent and could be reversed after the withdrawal of cortisol treatment.